Parking Space Needs Analysis Tamini Square Mall and Performance Roadway Pondok Gede, Jakarta - Widodo Budi Dermawan; Bagas Pradita (NAROTAMA UNIVERSITY, Indonesia, 2020)
Jakarta is the capital city of Indonesia with a population of 10.46 million inhabitants (CBS, 2018). Tamini Square Mall located in East Jakarta has a population of approximately 2,916,018 people (BPS, 2018). Tamini Square Mall is a mall located in East Jakarta, precisely at the Crossroads Taman Mini Raya and Jalan Raya Pondok Gede were established in 2006. The total area of ??approximately 1,000 meter² consisting of 5 floors. Tamini Square Mall became one of the popular shopping center due to its strategic location and within walking distance of Pinang Ranti Terminal, Settlements, Central Offices, Schools and Recreation Taman Mini Indonesia Indah. The method used in this research is by way of observation. Observation method is a method by means of direct survey of spaciousness. It is absolutely necessary to know the actual conditions. The survey method is dilakukuan on this analysis, a method of recording the number of vehicles. Accumulation of the largest parking for cars on Sunday as many as 120 vehicles occurred between 16:00 to 16:59 pm, while on Sunday for a motor vehicle 382 takes place between 14:00 to 14:59 pm. The average duration of parking of vehicles is 4 hours 24 minutes for cars and 4 hours 18 minutes for the motor. The parking index was 89.55% for cars occurred on Sunday at 16:00 to 16:59 pm and 88.84 for motorcycles occurred on Sunday at 14:00 to 14:59 pm. The Turn Over parking is 3 vehicles / SRP / time observations for cars and 4 vehicle / SRP / observation time for the motor and it happened on a Sunday. Judging from the analysis Roads Raya Pondok Gede, East Jakarta for speed survey at peak hours in the morning, afternoon and evening in getting the level of service or Level of Service (LOS), namely C and D.